Juntar, separar, mostrar: memória e escrita da história no Museu do Ceará (1932 - 1976) - Oliveira, Ana Amélia Rodrigues de (2008)
This research aims to interpret the course of the Ceara History Museum, since its creation (in 1932) until 1976. It discusses the manners of its exposures and sees about its public education function, considering that the Museum works as an educational institution where the historical objects could teach about past ages. In this way this research also analyze the Ceara History Museum from onward the agreements and conflicts which collaborate with its creation, considering it as a result of the social relationships which define its uses in a certain age.